Suzuki–Miyaura Reactions of Halospirooxindole Derivatives. Issue 16 (23rd April 2015) - El Bouakher, Abderrahman; Allouchi, Hassan; Abrunhosa‐Thomas, Isabelle; Troin, Yves; Guillaumet, Gérald
Abstract: Starting from 5, 5′‐dihalo‐1′‐pentyl‐2 H ‐spiro[furo[2, 3‐ b ]pyridine‐3, 3′‐indolin]‐2′‐one, various 5, 5′‐di(het)aryl‐1′‐pentyl‐2 H ‐spiro[furo[2, 3‐ b ]pyridine‐3, 3′‐indolin]‐2′‐ones were synthesized through palladium‐catalysed cross‐coupling reactions. A large panel of boronic acids (aryl or heteroaryl) could easily be introduced, leading to a library of new 5‐ or 5′‐monosubstituted and 5, 5′‐disubstituted 1′‐pentyl‐2 H ‐spiro[furo[2, 3‐ b ]pyridine‐3, 3′‐indolin]‐2′‐ones. Abstract : A library of 5‐ or 5′‐monosubstituted and 5, 5′‐disubstituted 1′‐pentyl‐2 H ‐spiro[furo[2, 3‐ b ]pyridine‐3, 3′‐indolin]‐2′ones has been efficiently prepared through Suzuki–Miyaura reactions conducted under microwave conditions.